2013
DOI: 10.1142/s0218810413970034
|View full text |Cite
|
Sign up to set email alerts
|

Sesamoidectomy and Volar Plate Repair Using Suture Anchor for Hyperextension Injury of the Metacarpophalangeal Joint of the Thumb

Abstract: A retrospective study for the combination of suture anchor and selective sesamoidectomy for treating volar instability of the metacarpophalangeal joint (MCPJ) of the thumb. Eleven patients with hyperextension of the MCPJ of the thumb underwent volar plate repair using a volar or voloradial approach. All the patients were reviewed radiologically and clinically using both objective and subjective criteria. The patients presented with sesamoid fractures (n = 2), sesamoid subluxation (n = 1), isolated volar plate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…If the PP of the thumb does not heal in proper position, prehensile function is lost and causes considerable functional impairment, which can progress to osteoarthritis. 24 Chronic instability of PP with persistent symptoms despite nonsurgical treatment requires surgery. Several techniques have been described: capsulodesis, sesamoid arthrodesis, and repair of PP with removable sutures or sutures in situ, with local tissue or tendon grafts.…”
Section: Discussionmentioning
confidence: 99%
“…If the PP of the thumb does not heal in proper position, prehensile function is lost and causes considerable functional impairment, which can progress to osteoarthritis. 24 Chronic instability of PP with persistent symptoms despite nonsurgical treatment requires surgery. Several techniques have been described: capsulodesis, sesamoid arthrodesis, and repair of PP with removable sutures or sutures in situ, with local tissue or tendon grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al reported the largest series of fractures to date (8). The MCP joint of the thumb was the most involved (59 cases): in 31 cases, the fractured sesamoid bone was the ulnar, in 17 the radial, and in 5 both ulnar and radial, whereas in 6, it was not reported, Other sesamoid bone fractures of the hand included 4 cases of the MCP joint of the little finger, 3 of the MCP joint of the index finger, and 1 of the MCP joint of the fourth digit . Although in the literature, fracture of the ulnar sesamoid bone of the thumb is the most reported, in our series, the radial one was more frequently injured (9 of 11 cases).…”
Section: Discussionmentioning
confidence: 99%
“…However, the thumb MCP joint volar plate differs from the proximal interphalangeal joint because there is no flexor sheath proximal to the plate. Thus, no strong check rein ligaments are present [ 3 , 4 ]. The palmar ligaments consist of a thick fibrocartilaginous part distally, but in its proximal end, the volar plate becomes membranous and blends with the volar capsule, which is attached to the head of the metacarpal bone.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ligament injury most often occurs in the proximal end of the ligament, in the metacarpal head [ 3 5 ]. Injury to the MCP joint volar plate of the thumb can result in serious functional impairment, producing pain and disability in the form of reduced pinch and grasp power, especially when it is not treated acutely and progresses into a chronic condition [ 3 , 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%